La cittadinanza europea: diritti, pratiche, appartenenze - Baglioni, Lorenzo Grifone (SocietàMutamentoPolitica, 2010)
The paper proposes a sociological approach to citizenship based on an analysis of the subject’s ability to develop and become autonomous, more typically given in addition to the formal theory of rights, specifically taking into consideration the particular material practices of individuals. This triggers a debate on welfare as a driver of citizenship, that with the scope to adjust the inclusive sense of the contemporary social context, points out to the merger and acquisition plurals. In the frame of our days, this analysis highlights the different spaces of citizenship within which individual action takes shape and develops membership. Alongside the new European area and of the consolidated national space, the renewed importance of local context emerges. It’s in the city, a place of opportunity, but also of tensions, that are brought to light the features of an inclusive society potentially capable of making the individual a true European.